A Bucket LBVH Construction and Traversal Algorithm for Volumetric Sparse Data - Fernandes, Igor Batista; Walter, Marcelo (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI); 2020: Anais da XXXIII Conference on Graphics, Patterns and Images, 2020)
Many volumetric rendering algorithms use spatial 3D grids as the underlying data structure. Efficient representation, construction, and traversal of these grids are essential to achieve real-time performance, particularly for time-varying data such as in fluid simulations. In this paper, we present improvements on algorithms for building and traversing Bounding Volume Hierarchies (BVH) designed for sparse volumes. Our main insight was to simplify data layout representation by grouping voxels in buckets, preserving their spatiality using Morton codes, instead of using bricks, as current solutions use. Our solution does not use pointers nor stacks, allowing for its usage directly on computing shaders and provides, on average, 9.3x improvement in construction speed, compared with state-of-the-art approaches for Linear Bounding Volume Hierarchies (LBVH).